Honorary Board Of The Regional Competence (DKD) In The Installation Procedures For Nameplate Of Notary In Sukoharjo District - Adi Candra Saputra; Maryanto Maryanto (Jurnal Akta, 2019)
The purpose of this study was to: 1) To determine the competence of the Regional Ethics Council (DKD) under the Act in force nowadays. 2) To determine the barriers and solutions implementation competence Regional Honor Council (DKD) in the installation nameplate notary. The data used in this study are primary data, secondary data and data that can support tertiary, which is then analyzed by the method of normative.Based on the results of data analysis stuffed in that: 1) the Honorary Council of Regions in Sukoharjo district authorities to build on the notary in the territory that is Sukoharjo against the code of professional conduct notary, as well as to investigate and adjudicate on members of notaries who have problems related to violations of the code of professional conduct notary in the decision can in the form of a. Coaching, oral or written warning, b. Stopping notary within a certain period, c. Dishonorable discharge. 2) Barriers occurring in the implementation of competence honorary board area Particularly in the area Sukoharjo need for affirmation should have from the beginning of a notary at the time of the oath-taking should be informed related to the code of conduct in this regard the implementation of the nameplate notary, only drawback at the time of the decision oath, honor council areas were excluded.Keywords: Competence of the Regional Ethics Board; Board Name Notaries; Notary